PENGUATAN PENDIDIKAN KARAKTER PADA ANAK SEKOLAH DASAR - Dwi Saputra, Agra; Tunnafia, Alanisa (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
Character education in elementary school children has a very important role in shaping children's personality and morals from an early age. Some of the strategies described include the integration of character values in the curriculum, the development of a supportive school environment, and the active role of teachers and parents in the formation of children's character. This research uses a qualitative approach with a case study method in several elementary schools in Indonesia. Data were obtained through in-depth interviews, participatory observation and document analysis. The results show that strengthening character education in elementary school children requires close cooperation between schools, families and communities. Factors such as school leadership, school culture and parental involvement are very influential in this process. In conclusion, character education should be an integral part of the basic education system to produce a generation that has strong character, integrity and is able to face future challenges. The implication of this study is the need for improved policies and more effective practices in supporting the strengthening of character education in primary schools.